Exploring the role of aging in the relationship between obstructive sleep apnea syndrome and osteoarthritis: Insights from NHANES data - Luo, Xin; Chen, Minghong; Xu, Jinghong (Frontiers in Medicine, 2024)
Background: Osteoarthritis (OA) is characterized by high morbidity and disability. Given studies have illuminated OA is correlated with age-related diseases, few research showed the potential relationship between OA and obstructive sleep apnea syndrome (OSAS). OSAS is featured by intermittent hypoxia and hypercapnia, we hypothesized these stressors induced ageing and increased OA prevalence.The study included 10641 participants from NHANES dataset in 2005-2008 and 2015-2018 years. The correlation between OSAS and OA was analyzed by multivariable logistic regression, calculated aging-related biomarkers and explored aging role by mediation analysis. Results: OSAS elevated the risk of OA (for quartile 4 vs. quartile 1, OR 2.31, 95%CI 1.34 to 3.99; P for trend = 0.004) after adjusting covariates; in 20-59 and > 60 years subgroup with OSAS patients had similarly trend (for quartile 4 vs. quartile 1, OR 5.69, 95%CI 2.75 to 11.8; P for trend < 0.001; OR 2.42, 95%CI 1.23 to 4.76; P for trend = 0.004, respectively). Further mediation analysis revealed that aging acted as a mediator between OA and OSAS (Biological age and phenotypic age mediation proportion were 13.82% and 52.94%, P < 0.001).These findings suggested people who had OSAS may boost the prevalence of OA and aging was also involved.